AL-QUR’AN MEMANDANG ISU ANTI BULLYING “Studi Penafsiran Tematik Ayat-Ayat Tentang Anti Bullying” - Li Izza Diana Mauzila (Al-Munir: Jurnal Studi Ilmu Al-Qur'an dan Tafsir, 2022)
This study aims to find out how the Qur'an views the issue of anti-bullying. The widespread use of social media makes it easy for people to hurl insults and insults at others. Both physically and mentally. whereas basically humans have been created so perfectly by Allah swt. The Qur'an which functions as a guide for everyday life has actually discussed the prohibition of bullying behavior. therefore, at least there is empathy that will be discussed in this study. First, what is the definition of bullying. second, what are the verses of the Qur'an that discuss the prohibition of bullying. third, how is the interpretation of the verses prohibiting bullying. fourth, how is the solution of the Qur'an against bullying behavior. This study is a literature review with qualitative research methods. While the approach used is a thematic approach. The results of this study are as discussed above, it is explained that the Qur'an does not explicitly explain the word bullying. It's just that the act of hurting other people, making fun of, mocking and criticizing are actions that are similar to the term bullying and are found in several verses in the Qur'an. Likewise with the solution to bullying, the Qur'an has explained it clearly and completely. Keyword : Anti-bullying, tafsir al-Qur’an, tematik